Co-gasification of glycerol/fat mixtures in a downflow fixed bed reactor: Preliminary results - A. Almeida; R. Pil\~ao; E. Ramalho; A. Ribeiro; C. Pinho (Energy Reports, 2020)
The aim of this work was to assess the technical viability of glycerol/fat co-gasification. The gasification performance was studied in a downflow fixed bed reactor using steam as oxidizing agent. Tests were performed with a mixture of 10% of fat and 52% of water, and the effect of temperature was evaluated in the 800~C to 950~C range. Samples of dry gas from the gasifier were collected and analysed by gas chromatography in order to determine the CO, CO2, CH4 and H2 content. The results revealed that the co-gasification of glycerol/fat mixtures seems to be a feasible technical option. Best results of the gasification parameters were obtained at the highest tested temperature, 950~°C.
Keywords: 330; Animal fat; Co-gasification; Crude glycerol; Fixed bed; Steam reforming